SUPERVISI AKADEMIK DI SMA NEGERI 1 KETAPANG - Misliyani Misliyani; Aswandi Aswandi; Wahyudi Wahyudi (Universitas Tanjungpura, 2021)
AbstractAcademic supervision is a series of activities to help teachers develop their ability tomanage the learning process, assess and foster teachers in order to improve the qualityof the learning process. This study aims to describe the implementation of academicsupervision in SMA Negeri 1 Ketapang. This research uses a qualitative approach witha type of case study. Sources of data are the principal, the vice principal in thecurriculum field, the vice principal in the field of student affairs, and 1 senior teacher.Methods of data collection by interview, observation, and document study. Dataanalysis used interactive data analysis, namely data reduction, data presentation andverification. Test data validity through credibility, transferability, dependability andconfirmability tests. The results showed that: academic supervision planning wascarried out through program preparation, supervision schedules, and socialization onthe importance of academic supervision. Supervision is carried out based on apredetermined schedule, instrument preparation, and supervision is carried outindividually and in groups. Evaluation of academic supervision through assessment oflearning devices, taking notes after supervision. The obstacles that occur include someteachers who are apathetic and feel that in the implementation of this supervision, theyare only looking for their mistakes, the lack of teaching aids and learning media areother obstacles in the implementation of supervision. Efforts to overcome obstaclesinclude the principal providing guidance, collaborating with the MGMP, taking steps tocreate a harmonious relationship, and optimizing existing facilities and infrastructure.Keywords: Academic, Educational Supervision, Supervision